PEREKAYASAAN SISTEM PENCITRAAN MATERIAL DI DALAM REAKTOR PETROKIMIA DENGAN TEKNIK SERAPAN SINAR GAMMA - Rony Djokorayono; Indarzah Masbatin Putra; Usep Setia Gunawan (BATAN, 2013)
Formation material contained in petrochemical reactor composed of ethylene gas, hydrogen gas and diluent, gas once it is processed at a pressure of 32 bar and a temperature of between 60 º C to 100 º C will produce hydrocarbons. The hydrocarbons die in the form of slurry with a density of between 600 gr/dm3 to 1200 gr/dm3, In the uncontrolled process the hydrocarbons will clot and causing reactor operation stopped because clogged by the clot material. In order the material not to clot, it required imaging detection system that describes the condition of the material in the reactor. Nuclear aplication method to describe the condition of the material in the reactor is simply by gluing several gamma detector outside the walls of the reactor and placing a 137Cs gamma sources amid type reactor process. It has been designed a prototype imaging system with the material in the petrochemical reactor gamma ray absorption technique composed of 137Cs gamma radiation source which is placed in the middle of the reactor, while the gamma radiation that comes out of the gamma source detected by a detector located outside the vessel surrounding the process. There are 12 gamma detectors and the gamma radiation intensity received is proportional to the fluctuation of the material contained within the reactor process. The results of measurements of the twelve detectors are processed by computer to be its dynamic state information material in the reactor process, while the profile monitor display measurement results in the form of two-dimensional topography. PEREKAYASAAN SISTEM PENCITRAAN MATERIAL DI DALAM REAKTOR PETROKIMIA DENGAN TEKNIK SERAPAN SINAR GAMMA, Formasi material yang terdapat di dalam reaktor petrokimia terdiri dari gas ethylene, gas hidrogen dan gas diluent, setelah diproses pada tekanan 32 bar dan temperatur antara 60ºC sampai 100ºC membentuk senyawa hidrokarbon. Senyawa hidrokarbon yang terbentuk berupa slurry dengan densitas antara 600 gr/dm3 sampai 1200 gr/dm3, bila hasil prosesnya tidak terkendali maka senyawa hidrokarbon yang terbentuk akan menggumpal, serta menyebabkan operasi reaktor terhenti karena tersumbat oleh material yang menggumpal. Agar material tidak sampai menggumpal diperlukan sistem deteksi pencitraan yang menggambarkan kondisi material di dalam reaktor. Metoda teknik nuklir dapat menggambarkan kondisi material di dalam reaktor hanya dengan menempelkan beberapa detektor gamma di luar dinding reaktor serta menempatkan sebuah sumber gamma di tengah reaktor. Telah dirancang prototip sistem pencitraan material di dalam reaktor petrokimia dengan teknik serapan sinar gamma yang tersusun dari sumber radiasi gamma 137Cs yang ditempatkan di tengah reaktor. Pancaran radiasi gamma dari sumber gamma dideteksi oleh detektor yang berada disekeliling luar bejana proses, yang berjumlah 12 unit detektor gamma. Intensitas radiasi gamma yang diterima akan sebanding dengan fluktuasi material yang terdapat di dalam reaktor. Hasil pengukuran dari ke duabelas detektor, oleh komputer akan diolah untuk memberikan informasi dinamis keadaan material di dalam reaktor dengan profil tampilan monitor hasil pengukuran berbentuk topografi dua dimensi.